2006
DOI: 10.2118/06-10-05
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Stress and Strain Due to Gas Sorption/Desorption and Their Effects on In Situ Permeability of Coalbeds

Abstract: Most past studies on coal shrinkage/swelling due to gas adsorption/ desorption were based on experiments under no constraint conditions. In this paper, the changes of stress and strain measured on one coal specimen under uniaxial compression in a vacuum and under axial constraint conditions during CO2 adsorption are presented and numerically simulated. The simulation results show that a linear elastic deformation model, suitable to isotropic continuum media but widely assumed in analytical permeability models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…The joint shear and normal stiffness for the bedding planes, face and butt cleat were set to 40.0 GPa/m (Gu and Chalaturnyk, 2006). The joint friction and dilation angles were set equal for all joints and were 25°and 5.0°r espectively.…”
Section: Dfn and Joint Propertiesmentioning
confidence: 99%
“…The joint shear and normal stiffness for the bedding planes, face and butt cleat were set to 40.0 GPa/m (Gu and Chalaturnyk, 2006). The joint friction and dilation angles were set equal for all joints and were 25°and 5.0°r espectively.…”
Section: Dfn and Joint Propertiesmentioning
confidence: 99%
“…The currently published permeability models can be generally classified into two types: analytical permeability models, mainly based on geomechanics theory combined with empirical or semi-empirical analysis (Gray, 1987;Harpalani and McPherson, 1985;Palmer, 2009;Puri and Seidle, 1991;Durucan, 2004, 2010;Shi et al, 2014;Somerton, 1975) and coupled permeability models, which include continuum medium coupled (CMC) model and discontinuum medium coupled (DMC) model. Gu and Chalaturnyk (2006) compared these models and suggested that the DMC model provides better estimates of permeability and production than analytical models because it includes the influences of many factors, such as discontinuity and anisotropy.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Of the existing models, the most commonly used are the ones presented by Palmer and Mansoori [12] (P&M model), Shi and Durucan [13] (S&D model), and Cui and Bustin [14] (C&B model). Gu and Chalaturnyk [15] and Palmer [16] have reviewed commonly used analytical permeability models, and made a classification based on whether a model is strainbasedor stress-based. For the strain-based models, the coal/rock strain is the cause for any change in flow behavior; In CBM reservoirs, gas desorption-induced matrix shrinkage and mechanical compaction induced by an increase in effective stress with gas depletion are the two factors influencing the volumetric strain of the coal matrix, and in turn, changes in cleat porosity and cleat permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Gu and Chalaturnyk [15] offered a distinction based on whether a model is strain-based or stress-based. The original P&M model and improved P&M model are based on the change in volumetric strain due to the desorption of methane, thus resulting in changes in cleat porosity and permeability.…”
mentioning
confidence: 99%